2011
DOI: 10.4103/0974-7796.75870
|View full text |Cite
|
Sign up to set email alerts
|

The validity of testicular catch-up growth and serum FSH levels in the long-term postoperative assessment of laparoscopic varicocele correction in adolescents

Abstract: Background:Postoperative assessment after varicocele surgery in adolescence is commonly centred around catch-up growth of the testis. There is paucity of evidence on the correlation of catch-up growth with underlying testicular function in these patients.Aims:To assess the reliability of catch-up growth of the testis as an indicator of normalization of testicular function and the utility of serum FSH levels in the long-term postoperative assessment of varicocele surgery in adolescence.Materials and Methods:Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…It was suggested that hyperplasia of Leydig cells is the poor prognostic factor for fertility. [40] Additionally, the mean testosterone concentration of men with varicocele older than 30 years was found to be significantly lower than that of younger patients with varicocele, whereas this trend was not observed in men without varicocele. Conversely, significant increase in mean testosterone levels was documented after varicocelectomy without concomitant increase in the serum levels of leutinising hormone (LH) and follicle-stimulating hormone (FSH).…”
Section: Evidence Synthesis For This Reviewmentioning
confidence: 97%
See 4 more Smart Citations
“…It was suggested that hyperplasia of Leydig cells is the poor prognostic factor for fertility. [40] Additionally, the mean testosterone concentration of men with varicocele older than 30 years was found to be significantly lower than that of younger patients with varicocele, whereas this trend was not observed in men without varicocele. Conversely, significant increase in mean testosterone levels was documented after varicocelectomy without concomitant increase in the serum levels of leutinising hormone (LH) and follicle-stimulating hormone (FSH).…”
Section: Evidence Synthesis For This Reviewmentioning
confidence: 97%
“…[1138] Or if asymptomatic, it may not present until during investigation of male sub-fertility. [3940] With the recent advancement of imaging technology, most of the varicoceles are diagnosed nowadays incidentally while undergoing scrotal ultrasonography for testicular related pain or other symptoms. [4142]…”
Section: Evidence Synthesis For This Reviewmentioning
confidence: 99%
See 3 more Smart Citations